The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013 Annual International Conference on Emerging Research Areas and 2013 International Conference on Microelectronics, Communic 2013
DOI: 10.1109/aicera-icmicr.2013.6575936
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tunnel currents through SiO<inf>2</inf>, HfO<inf>2</inf>, Ta<inf>2</inf>O<inf>5</inf>, ZrO<inf>2</inf> and Dy<inf>2</inf>O<inf>3</inf> dielectrics in MOS devices for ultra large scale integration using first principle calculations

Abstract: The work presented in this paper focuses on the effects of high leakage current in field effect transistors and the possible ways to play down with the leakage currents. This paper combines density functional theory and non equilibrium Green's function formalism to perform atomic scale calculation of tunnel currents through SiO 2, HfO 2 , Ta 2 O 5, ZrO 2 and Dy 2 O 3 dielectrics in MOSFETs. The tunnel currents for different bias voltages applied to Si/Insulator/Si systems have been obtained along with tunnel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…As a possible replacement for gate dielectrics, Dy2O3 is one of the most promising REO materials owing to its high dielectric constant (k = 14-18), a large energy band gap (4.9 eV), and thermal and chemical stability with silicon [14]- [16]. Researchers have already reported that Dy2O3 exhibits promising performance in gate dielectric applications [5], [17], [18]. However, together with these initial studies, the stability of the device should be investigated in various environments including the irradiation field to test the device reliability.…”
Section: Introductionmentioning
confidence: 99%
“…As a possible replacement for gate dielectrics, Dy2O3 is one of the most promising REO materials owing to its high dielectric constant (k = 14-18), a large energy band gap (4.9 eV), and thermal and chemical stability with silicon [14]- [16]. Researchers have already reported that Dy2O3 exhibits promising performance in gate dielectric applications [5], [17], [18]. However, together with these initial studies, the stability of the device should be investigated in various environments including the irradiation field to test the device reliability.…”
Section: Introductionmentioning
confidence: 99%